2006
DOI: 10.1152/physiolgenomics.00068.2006
|View full text |Cite
|
Sign up to set email alerts
|

Murine weight loss exhibits significant genetic variation during dietary restriction

Abstract: We present genetic analyses of murine weight loss during dietary restriction (DR) for females eating 60% ad libitum (AL). We examined 5 cohorts across 81 different strains (22 strains tested twice) that included the LXS and LSXSS recombinant inbred strains, the LXS parental strains ILS and ISS, and the classical inbreds 129S6, A, BALB/c, C57BL/6, C3H, and DBA. Weight loss exhibited highly significant genetic variation, with DR body weights ranging from ∼60 to ∼85% of AL body weight. This variation was not expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 25 publications
4
44
0
Order By: Relevance
“…Murine studies offer 'proof of concept' that, at least for mice, weight loss sensitivity during DR is under genetic control with a heritability of 40-50% (Rikke et al, 2006). An ability to identify WLR or WLS phenotypes among Equidae, may offer similar potential for directed therapeutics as well as suggesting a potential basis for selective breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Murine studies offer 'proof of concept' that, at least for mice, weight loss sensitivity during DR is under genetic control with a heritability of 40-50% (Rikke et al, 2006). An ability to identify WLR or WLS phenotypes among Equidae, may offer similar potential for directed therapeutics as well as suggesting a potential basis for selective breeding.…”
Section: Discussionmentioning
confidence: 99%
“…DR food intake in this study was carefully controlled to be 60% of AL, as determined separately for each strain, with each mouse housed singly (12,13,15). The food intake of each AL mouse was measured each week over the entire study, with the food weights being collected at approximately the same time of day each week.…”
Section: Strainsmentioning
confidence: 99%
“…More recently, we also demonstrated that there is marked genetic variation in the response of BW to DR, with the strain means for BW ranging from about 60 to 85% of the AL controls (15). The variation in these responses is not explained by trivial factors, such as the strain differences in absolute food intake, feces:food ratios, feces calorimetry, gross motor activity, or AL percent body fat (12,13,15). Therefore, in this study, we asked to what extent the T b and BW responses are being coordinately modulated in these strains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because so much is known about the effects of CR on laboratory rodents, they would initially be a useful host to use for research with intact pathogens. Of course, there is variation in response to CR even among inbred mouse strains (Turturro et al 1999;Brochmann et al 2003;Rikke et al 2003Rikke et al , 2006, as well as between males and females (Wu et al 2003a;Shi et al 2007). Mouse strain and sex also influence susceptibility to pathogens (Zuk and McKean 1996;Morales-Montor et al 2004;, and these effects are pathogen-specific.…”
Section: General Considerations When Using Intact Pathogensmentioning
confidence: 99%